2014
DOI: 10.12705/632.6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphological diversity of Sphagnum angustifolium, S. flexuosum and S. fallax in Europe

Abstract: Molecular and morphological evolution of species may be decoupled which can lead to contrasting delimitation of taxonomic units based on morphological and genetic characters. The moss genus Sphagnum (peat mosses) provides a good example in which morphological and genetic characters often contradict each other. We investigated morphological and genetic variability within a highly polymorphic and taxonomically controversial species complex of the genus Sphagnum in order to reveal the ultimate causes of discordan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
(41 reference statements)
0
8
0
2
Order By: Relevance
“…Interspecific hybridization has been already documented in the subgenus Acutifolia by Cronberg (1998), Flatberg et al (2006, and Natcheva and Cronberg (2007). Microsatellite data further revealed hybridization within the subgenus Cuspidata (Szurdoki et al 2014), and hybridization among species from different subgenera has even been shown (Karlin et al 2009(Karlin et al , 2014. The ability to hybridize may not be uniform across the subgenus Acutifolia, and the genetic data suggest that S. rubellum and S. warnstorfii tend to hybridize easily (Shaw and Cox 2005).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Interspecific hybridization has been already documented in the subgenus Acutifolia by Cronberg (1998), Flatberg et al (2006, and Natcheva and Cronberg (2007). Microsatellite data further revealed hybridization within the subgenus Cuspidata (Szurdoki et al 2014), and hybridization among species from different subgenera has even been shown (Karlin et al 2009(Karlin et al , 2014. The ability to hybridize may not be uniform across the subgenus Acutifolia, and the genetic data suggest that S. rubellum and S. warnstorfii tend to hybridize easily (Shaw and Cox 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Microsatellite data further revealed hybridization within the subgenus Cuspidata (Szurdoki et al. ), and hybridization among species from different subgenera has even been shown (Karlin et al. , ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S. flexuosum is morphologically similar to S. fallax , but genetically distinct (Szurdoki et al. ). Already, Rybníček () reported S. flexuosum from fens with pH 5 or even pH 6.…”
Section: Discussionmentioning
confidence: 99%